Plastibell circumcision of 2,276 male infants: a multi-centre study - Jimoh, Bioku Muftau (Pan Afr Med J, 2016)
INTRODUCTION: The World Health Organization's manual on male circumcision listed Plastibell technique as a well-proven paediatric method with respect to the results and complications. Although, literatures abound on its wide acceptability, there are few multi-centered reports from this environment. The objective was to evaluate the cases of infant circumcision by Plastibell device from two medical institutions. METHODS: All consecutive infants who had Classical Plastibell Circumcision (PC) at the Federal Staff Medical Centre, Abuja and the Lagos State University Teaching Hospital, Ikeja between February 2011 and June 2015 were included in this cross-sectional study. The procedures were performed by surgical registrars and medical officers after ninety minutes of topical anesthesia to the penis. Data harvested from the standard proforma were analysed using Statistical Package for Social Science 20.0 for window. RESULTS: A total of 2,276 infants had classical PC within the study period. Their ages at circumcision ranged from 4 days to 3 months with a mean age of 17 days. Majority of the boys were circumcised at second week of life (n=1,394,61.2%). All the cases were performed for religious (53%) and cultural (47%)reasons. The most common Plastibell size deployed was 1.3cm (n=1,040, 45.7%) while 1.6cm was the least commonly used ring (n=10, 0.4%). The mean time for device to fall-off was 6 days (range 4-12 days). There was no correlation between the age at circumcision and Plastibell size. We recorded an overall complication rate of 1.1% with postoperative bleeding leading the pack (n=12, 48%). No case of urethrocutaneous fistula was seen. We detected 17 cases (0.7%) of distal hypospadias in whom circumcisions were postponed till the time of hypospadias repairs. CONCLUSION: The main indication for infant circumcision in our environment was religious. The PC has good safety profile with few easily correctable early complications. Detailed attention to placement of ligature, selection of appropriate Plastibell size and adequate parental education are key to preventing post-procedure mishaps.